Molecular biology and pathogenesis of human polyomavirus infections - Dörries, K (Developments in biological standardization, 1998)
The two human polyomaviruses JC and BK are ubiquitous in the human population. Primary infection leads to lifelong persistence in the kidney, the CNS and in lymphoid cells. Virus is shed into the urine and is transmitted at least in part by the oral route. Under limited changes of the immunological state persistent polyomavirus infection is activated to an asymptomatic virus production. However, in severe long-lasting immunosuppression, highly effective virus multiplication can be accompanied by extended cytolytic damage of viral target cells leading to fatal disease. Whereas BKV is associated with severe urogenital disorders, JCV affects the CNS, leading to progressive multifocal leukoencephalopathy (PML). Although the number of PML cases is steadily increasing because of the AIDS epidemic, the mechanisms responsible for the change from asymptomatic-activated to the diseased state are not yet understood. As a possible pathogenic factor, the role of genomic heterogeneity of the transcriptional control region in the induction of disease is discussed.